2023
DOI: 10.3390/ijpb14020042
|View full text |Cite
|
Sign up to set email alerts
|

Histological Approach to the Study of Morphogenesis in Callus Cultures In Vitro: A Review

Abstract: The use of in vitro callus cultures as experimental model systems allows us to get closer to understanding the patterns and features of morphogenesis in intact plants. In this regard, the problem of realizing the morphogenetic potential of callus cells due to their pluri- and totipotency properties is of great interest. To solve this problem, it is important to use the histological approach, which involves studying the structures of developing tissues, organs and organisms in their interactions and relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…In contrast to the compact callus tissue, the friable callus tissue was composed of cells with sharp, uneven edges (Figure 3). The compact callus tissue had inclusions of densely located cells (Figure 3), which are commonly referred [31] to as meristemoids. Chloroplasts with a clearly exhibited granal structure were observed in the cells of the compact callus tissue; however, these cells showed strongly marked signs of senescence-very thin layer of cytoplasm and cytoplasm sequestration, rupture of the vacuolar membrane, delamination of the cytoplasm from the cell wall and targeting of organelles (including chloroplasts) into vacuoles, with a low number or absence of mitochondria (Figure 4A,B,D,E).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the compact callus tissue, the friable callus tissue was composed of cells with sharp, uneven edges (Figure 3). The compact callus tissue had inclusions of densely located cells (Figure 3), which are commonly referred [31] to as meristemoids. Chloroplasts with a clearly exhibited granal structure were observed in the cells of the compact callus tissue; however, these cells showed strongly marked signs of senescence-very thin layer of cytoplasm and cytoplasm sequestration, rupture of the vacuolar membrane, delamination of the cytoplasm from the cell wall and targeting of organelles (including chloroplasts) into vacuoles, with a low number or absence of mitochondria (Figure 4A,B,D,E).…”
Section: Resultsmentioning
confidence: 99%
“…This approach is an important tool for understanding structural changes at the cellular level during genetic reprogramming for organogenesis and somatic embryogenesis. This study also revealed the dedifferentiation process in competent cells of highly differentiated mature tissues, identified the zone within the callus from which the acquisition of pluripotency or totipotency occurs, and, most importantly, revealed the spatial and temporal development of vegetative shoots, floral organs, and somatic embryos (Kruglova et al, 2023). Moreover, anatomical studies during the regeneration process will explain the role of programmed cell death (PCD) and polyphenol accumulation during the origination and pattern formation of shoot buds and somatic embryos.…”
mentioning
confidence: 81%
“…(Awal et al, 2013) and Arabidopsis thaliana (Cheng et al, 2010), but no one has previously reported co‐occurrence of shoot, flower, and somatic embryo differentiation from a single piece of callus in any plant system. The simultaneous differentiation of vegetative and reproductive organs, together with somatic embryogenesis, depends on differential genetic reprogramming of existing somatic cells of the callus and the acquisition of either cellular totipotency or pluripotency from the stem cell niche (Kruglova et al, 2023). To learn the tangible facts, it is pertinent to study the ontogeny of the redifferentiation process based on sequential histological observations.…”
Section: Introductionmentioning
confidence: 99%
“…These are "young" cells that are formed after the transfer of callus to a fresh nutrient medium [49]. It is believed that their formation is due to the functional activity of the so-called "meristematic zone" of plant calluses [50].…”
Section: Morphological Parameters Of Tea Callus Culturesmentioning
confidence: 99%